Boosting the Areal Capacity of Titanium‐Manganese Single Flow Battery by Fe2+/Fe3+ Redox Mediator. Issue 1 (22nd December 2022) - Nan, Mingjun; Wu, Min; Liu, Yuqin; Qiao, Lin; Zhang, Huamin; Ma, Xiangkun
Abstract: Aqueous manganese‐based flow batteries (AMFBs) have attracted great attention due to the advantages of low cost and environmental friendliness. Extending the cycle life of AMFBs has long been a challenging theme. The titanium‐manganese single‐flow batteries (TMSFB) are promising due to their special structure and electrolyte composition. However, TMSFB with high areal capacity faces capacity decay for unknown reasons. In this work, the capacity decay mechanism (accumulation and growth of MnO2 ) is clarified by a homemade in situ microscope system. Given that, a redox mediator of Fe 2+ /Fe 3+ is specially designed to boost the areal capacity of TMSFB without side reaction. The directional promoting principle of the Fe 2+ /Fe 3+ is elaborated in detail. Fe 2+ chemically reacts with the residual MnO2 to form Fe 3+, which is reduced to Fe 2+ by the electrochemical reaction. And then Fe 2+ continues reacting with MnO2 until MnO2 is consumed completely. As a result, the TMSFB with the areal capacity of ≈55 mA h cm −2 can stably operate at a current density of 40 mA cm −2, which is the highest areal capacity reported in aqueous manganese‐based batteries. This work provides a new strategy for boosting the capacity of manganese‐based batteries, shedding light on the improvement of other deposition‐type batteries. Abstract : The decay mechanism of titanium‐manganese single flow batteries (TMSFB) is observed by an in‐situ microscope system. The accumulation and growth of MnO2 particles in each cycle greatly increases the polarization of TMSFB and exacerbates the capacity decay. With the introduction of a Fe 2+ /Fe 3+ redox mediator, the residual MnO2 particles could be reduced completely without side reaction, achieving excellent cycling stability and areal capacity.